Tindakan Benturan Kepentingan Yang Dilakukan Oleh Direksi Perusahaan Sebagai Bentuk Pelanggaran Prinsip Good Corporate Governance - Destria, Dhita (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
All principles of Good Corporate Governance can support the realization of Good Corporate Governance in order to prevent abuse of power and illegal acts committed by the organs of the company. Demands faced limited liability company is about transactions conducted by the relevant organs, in particular by the board of directors of a limited liability company with others having a close relationship with the board of directors of a limited liability company that raises a conflict of interest. That actions such as self dealing, accepting gifts or benefits include all forms of bribery and kick-back fee, peddling influence (influence pedding), utilizing company assets for personal benefit (using employer's propety for private advantage) and take advantage of confidential information (using confidential information) is some form of Conflict of Interest. Factors that cause the Conflict of Interest is the internal factors are derived from transactions Conflict of Interest is done inside the company may for personal benefit of its board of directors, while external factors are transactions Conflict of Interest made by the board of directors to gain own private not for profit company, but do it in silence and collusion.